Literasi Digital Tranformatif Berbasis Ideologi Muhammadiyah Untuk Mengatasi Gangguan Informasi Pada Gen Z Di Kota Bengkulu - Mely Eka Karina; Rifa’i (STAI Bumi Silampari, 2026)
This study aims to analyze the construction of transformative digital literacy based on Muhammadiyah ideology to overcome information disorder among Generation Z in Bengkulu City through the perspective of Social Cognitive Theory. This qualitative research with a transformative case study approach involved 24 Gen Z informants (aged 18-25 years) selected through purposive sampling. Data were collected through in-depth interviews, focus group discussions, and participatory observation (October-December 2025) and analyzed using thematic analysis with NVivo 14. The findings reveal a digital paradox: Bengkulu's Generation Z demonstrates high technical proficiency but struggles with critical literacy skills. The Transformative Digital Literacy Model (MLDT) integrates three components using Social Cognitive Theory (SCT), covering personal, behavioral, and environmental factors with Muhammadiyah values (tajdid, Al-Ma'un, progress). The implementation of the model through Tabayyun Workshops, the Digital Khalifah Program, and Moral Re-engagement Sessions showed substantial effectiveness: significant improvements in verification skills, constructive skepticism, and self-efficacy self-efficacy were observed through deep transformations in participants' understanding and information behavior. This research contributes to the integration of psychological theory with Islamic values and a contextually grounded digital literacy intervention model.